Novel combined thermodynamic cycle - Khalatov, A.A.; Stupak, O.S.; Grishuk, M.S.; Galaka, O.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
The novel thermodynamic cycle is suggested, by using a combination of the Maisotsenko and Ranque cycles. The experimental study has confirmed the superefficiency of the cycle that is greater than that of all currently known cycles.